Kotlin Programming Cookbook : Explore more than 100 recipes that show how to build robust mobile and web applications with Kotlin, Spring Boot, and Android. - Karanpuria, Rashi (Packt Publishing, 2018)
The Android team has announced first-class support for Kotlin. This acts as an added boost to the language and more and more developers are now looking into Kotlin for their application development. This recipe based book will be your guide to get a firm hold on the Kotlin Programming language.